Highly efficient and stable p-type ZnO nanowires with piezotronic effect for photoelectrochemical water splitting. (July 2019) - Cao, Chang; Xie, Xinxin; Zeng, Yamei; Shi, Shaohua; Wang, Guizhen; Yang, Liang; Wang, Cai-Zhuang; Lin, Shiwei
Abstract: Unremitting efforts have been made to develop high-performance photoelectrochemical (PEC) water-splitting system to produce clean hydrogen fuel using sunlight. In this work, a novel way, combining highly-ordered nanowires (NWs) structure and piezotronic effect of p-type ZnO has been demonstrated to dramatically enhance PEC hydrogen evolution performance. Systematic characterizations indicate that the Sb atoms uniformly dope into ZnO NWs and substitute Zn sites with the introduction of two zinc vacancies to form the shallow acceptor SbZn –2VZn complex. Detailed synchrotron-based X-ray absorption near-edge structure (XANES) experiments in O K-edge and Zn L-edge further confirm the formation of the complex, and theoretical calculation verifies the Sb 5+ state dominating the complex. The optimal photocurrent density of the 0.2Sb/ZnO-anneal NWs can reach −0.85 mA/cm 2 (0 VRHE ) which is 17.2 times larger than that of the n-ZnO NWs under sunlight illumination (100 mW/cm 2 ). Furthermore, the piezotronic effect can be introduced to regulate the charge separation and transfer in the ZnO NWs through modulating the band structure near the interface. The photocurrent density can further increase to −1.08 mA/cm 2 (0 VRHE ) under a 0.6% tensile strain, which is 27.4% enhancement with respect to the ZnO sample without strain. These results provide an efficient way to design and develop high-performance photoelectrodes toward PEC hydrogen evolution. Graphical abstract: Image 1 Highlights: PEC performance is enhanced by combining highly-ordered nanowires structure and piezotronic effect of p-type ZnO. Highly stable p-typed conduction has been achieved through uniformly doping Sb into ZnO NWs. Experimental and theoretical analyses demonstrate formation of the SbZn -2VZn complex with Sb 5+ states in Sb-doped ZnO NWs. Piezotronic effect can accelerate charge separation and transfer through modulating the band structure near the interface.